2013
DOI: 10.5507/bp.2013.043
|View full text |Cite
|
Sign up to set email alerts
|

STAT6 - polymorphisms, haplotypes and epistasis in relation to atopy and asthma

Abstract: Background. STAT6 has an important role in the IL-4 / IL-13 signalling pathway. Genome -wide association studies have shown that particular polymorphism (SNP) or haplotype variants of STAT6 as well as epigenetic gene modifications are associated with IgE level and asthma in childhood. Methods. A review of the available literature was performed to map out the function and signalling pathway of STAT6, studies of STAT6 SNPs association with susceptibility to asthma and atopy, covering the years 1997 -2012 were su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…This was a new association reported by TAGC, not previously implicated in any asthma GWAS, although we note this SNP has been reported as a putatively causal SNP discovered by GWAS of lung function 23,24 , and a number of linkage studies have pinpointed this chromosomal region in the early days of genome-wide investigations of asthma and atopy 2528 . In addition, markers in STAT6 have been identified by a number of candidate gene association studies 2932 . However, prior to the CAAPA analyses, this locus had not been replicated in independent asthma GWAS datasets.…”
Section: Resultsmentioning
confidence: 99%
“…This was a new association reported by TAGC, not previously implicated in any asthma GWAS, although we note this SNP has been reported as a putatively causal SNP discovered by GWAS of lung function 23,24 , and a number of linkage studies have pinpointed this chromosomal region in the early days of genome-wide investigations of asthma and atopy 2528 . In addition, markers in STAT6 have been identified by a number of candidate gene association studies 2932 . However, prior to the CAAPA analyses, this locus had not been replicated in independent asthma GWAS datasets.…”
Section: Resultsmentioning
confidence: 99%
“…46 Moreover, STAT6 polymorphisms have an important influence on IgE level and development of asthma. 47 Lau et al 48 has suggested that loss of STAT6 promotes autoimmune disease and atopy and STAT6 correlates with IgE level.…”
Section: Discussionmentioning
confidence: 99%
“…rs7574865 has been associated with numerous autoimmune diseases, as well as with psoriasis in our investigation, indicating that the common functional sequences are shared in those autoimmune diseases and that rs7574865 plays an important role in the immune system and may represent a potential target for the treatment of these diseases [4,37] . STAT6 has similarity with other STAT proteins and is one of the most common candidate genes associated with higher levels of IgE [38] . STAT6 is essential for the functional responses of Th2 cells by inducing 2 forms of the cytokines IL-4 and IL-13 [39,40] .…”
Section: Discussionmentioning
confidence: 99%